The collection of oat genetic resources held by VIR as a source of information on the history of cultivation and taxonomy of the genus, and breeding trends (a review) - I. G. Loskutov; E. V. Blinova; A. A. Gnutikov (Труды по прикладной ботанике, генетике и селекции)
Oat is one of the leading cereals cultivated in the world and in Russia; it has an important fodder and nutritional value. To preserve the entire crop agrobiodiversity worldwide, there is a network of genebanks that hold more than 200,000 oat accessions. International and national genebanks are located in all the world’s countries, but one of the largest oat collections is located in Russia.The global collection of the genus Avena L. (Oats) at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) is one of the largest worldwide and consists of over 13,000 accessions. The collection preserves and maintains live accessions of all cultivated oat species: A. sativa L., A. byzantina K. Koch, A. strigosa Schreb. and A. abyssinica Hochst., landraces, breeding lines, spring and winter forms, covered and naked genotypes, and all geographic diversity of 22 wild Avena spp. from 50 countries. This review provides historical background of the collection of cultivated and wild oat species, and who were the main donors of these holdings. The taxonomic system of the genus is briefly presented, which is used as a tool for efficient work and guaranteed safe preservation of accessions. Most of the cultivars developed in Russia have in their pedigree accessions obtained from the global collection of VIR. The passport database contains detailed information about all accessions of the collection, which makes it possible to improve the work with the oat collection, including safe preservation of accessions and their effective evaluation and use as source material for breeding in the leading breeding centers of Russia.Thus, the global oat collection at VIR has factual and potential value for the sustainable development of environmentally friendly agriculture, efficient processing of agricultural products, and production of safe and high-quality food products, including functional foods.